Comunidade de copépodes (COPEPODA:CRUSTACEA), na plataforma continental do Nordeste do Brasil - Campos, Carolina Coelho (2014)
The continental shelf of tropical zones is known as a transition area between the continent and the open sea. Copepods dominate the mesozooplankton community in most of subtropical and tropical marine waters. Little is known about its ecology in the continental shelf of the semiarid Brazilian northeast coast despite the recognized importance of these organisms. The study aimed to analyze the composition and spatial distribution of the copepod community on the continental shelf of the states of Ceará, Piauí and part of Maranhão. Sampling was carried out in July and October 2010 in continental shelf (inner, middle and outer), with a cylindricalconical net (300 µm). Three parallel to the coast profiles (A, B and C) were defined from the coast to the slope, each containing 18 stations. Thirty-eight species were found; 20 calanoids, 14 cyclopoids and 4 harpacticoids. The average density was 1,28 ± 12,71 ind./m³. The lowest value was 0,13 ind./m³ and the highest was 15,59 ind./m³. Among the organisms considered very frequent, the most important were Paracalanus aculeatus (adult and juvenile copepodite) and Corycaeus (Onychocorycaeus) giesbrechti. The latter occurred in 100% of samples. Endemic species in the Atlantic Ocean (Calanopia americana, Labidocera nerii and Farranula gracilis) and in Brazil (Acartia lilljeborgii and Pseudodiaptomus acutus) were found. The continental shelf of the semiarid coast (PCCS) showed typical species of estuarine/coastal, continental shelf and oceanic regions, characterizing this area as a transition zone. In PCCS, the characteristics found in the three profiles in relation of the total density of copepods (Profile A > Profiles B and C) and species richness (Profiles B and C > Profile A) showed differences in community structure in relation to distance from the coast. The profiles revealed differences in community structure and the low densities reflected the oligotrophy of the environment. The Venn diagram showed a greater number of common species in the profiles B and C. Oceanic influences were observed due to the presence, in profiles B and C, of species known to inhabit this environment. The distribution of certain species of copepods is considered good indicators of water masses. Overall, a low influence of the estuarine environment in PCCS was measured by the low densities typical species.